Is Guillain–Barré Syndrome Associated With COVID-19 Infection? A Systemic Review of the Evidence - Abdullahi, Auwal; Candan, Sevim Acaroz; Soysal Tomruk, Melda; Elibol, Nuray; Dada, Olumide; Truijen, Steven; Saeys, Wim (Frontiers in Neurology, 2021)
Background: There is emerging evidence that Guillain–Barré syndrome (GBS) may be associated with coronavirus disease 2019 (COVID-19) infection. The aim of this review was to investigate the strength of the evidence. Method: The review was registered in PROSPERO (CDR42020184822). Three electronic databases, MEDLINE, PubMed, and Web of Science, and three preprint servers, MedRvix, ChemRvix, and BioRvix, were searched from December 2019 to 24th September 2020. Studies were included if they were on COVID-19 and of any design. Articles that are reviews or opinion were excluded. The selection process was carried out using EndNote and Rayyan software. The main outcomes in the study were study design, sample size, sex, age, overall GBS symptoms, other COVID-19 symptoms, comorbidity, timing between infection and the onset of neurological symptoms, CT, MRI, and EMG results. Methodological quality of the studies was assessed using the McMaster Critical Review Form. The collected data was analyzed using qualitative synthesis. Findings: Fifty-one high-quality studies (mostly) consisting of 83 patients were included in the study. All of the patients (except in a very few) in the included studies had confirmed diagnosis of COVID-19. Similarly, the diagnosis of GBS was based on standard clinical, electrophysiological, and cerebrospinal fluid (CSF) criteria. Conclusion: GBS may be associated with COVID-19, and therefore, testing for COVID-19 is recommended in patients presenting with GBS during this pandemic.